The punisher's brain: the evolution of judge and jury - Hoffman, Morris B. (Cambridge studies in economics, cognition, and society, 2014)
"Evolution built us to punish cheaters. Without that punishment instinct, we would never have been able to live in small groups, and would never have realized all the significant benefits that small-group living conferred, including mutual defense, cooperative hunting, property, divisions of labor and economies of scale. In fact, to a large extent our notions of right and wrong, of empathy and compassion, of fairness and justice, all come from the tensions of group living, and thus indirectly owe their very existence to punishment. It may sound strange that one key to civilization is our willingness to punish each other, but every parent knows it's true. Every parent also feels the irresistible pull not to punish too much, and in fact maybe not to punish at all - to forgive - and this, too, is a remnant of evolution. Our punishment instinct is not so much a sword ready to fall as it is a finely tuned balance, sometimes susceptible to the gentlest of breezes"--